Discover a world of knowledge at Westonci.ca, where experts and enthusiasts come together to answer your questions. Get quick and reliable answers to your questions from a dedicated community of professionals on our platform. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.

Use the description below to find the equation of the hyperbola in standard form. Try making a sketch of the graph to help you. If a value is not an integer type it as a decimal rounded to the nearest hundredth.Standard form:\frac{(x-h)^2}{a^2} -\frac{(y-k)^2}{b^2}=1 Description:Center at (4,2); vertex at (9,2) and one focus at (4+ \sqrt[]{26} ,2) .The value for h is AnswerThe value for k is AnswerThe value for a is AnswerThe value for b is Answer

Use The Description Below To Find The Equation Of The Hyperbola In Standard Form Try Making A Sketch Of The Graph To Help You If A Value Is Not An Integer Type class=

Sagot :

We have to find the equation of the hyperbola in standard form.

The information we have is:

• Center: (4, 2)

,

• Vertex: (9, 2)

,

• Focus: (4+√26, 2)

From the center, we can derive the values for h and k, as the center of the hyperbola will be (h,k).

Then, h = 4 and k = 2.

We know have to use the information from the vertex and the focus to find parameters a and b.

We can start sketching the hyperbola and the points as:

As 4+√26 is approximately 9.1, the focus and the vertex are very close, as the vertex has x-coordinate x = 9.

We can now calculate the parameter a using the vertex as:

[tex]\begin{gathered} \text{vertex}=(9,2) \\ \Rightarrow\frac{(9-4)^2}{a^2}+\frac{(2-2)^2}{b^2}=1 \\ \frac{5^2}{a^2}+\frac{0^2}{b^2}=1 \\ \frac{5^2}{a^2}=1 \\ a=5 \end{gathered}[/tex]

We now have to calculate parameter b.

The only information we haven't used is the focus.

We can relate the focus coordinates to the equation as:

[tex]a^2+b^2=c^2[/tex]

where c is the focal distance.

This focal distance will be, in this case, the distance between the focus and the vertex.

We can express this as:

[tex]\begin{gathered} c=\sqrt[]{(x_v-x_f)^2+(y_v-y_f)^2} \\ c=\sqrt[]{(9-4+\sqrt[]{26})^2+(2-2)^2} \\ c=\sqrt[]{(5+\sqrt[]{26})^2} \\ c=5+\sqrt[]{26} \end{gathered}[/tex]

We can now calculate b as:

[tex]\begin{gathered} a^2+b^2=c^2 \\ b^2=c^2-a^2 \\ b^2=(5+\sqrt[]{26})^2-5^2 \\ b^2=5^2+2\cdot5\cdot\sqrt[]{26}+(\sqrt[]{26})^2-5^2 \\ b^2=10\sqrt[]{26}+26 \\ b^2\approx77 \\ b\approx\sqrt[]{77} \\ b\approx8.77 \end{gathered}[/tex]

Then, we can complete the equation as:

[tex]\frac{(x-4)^2}{5^2}-\frac{(y-2)^2}{8.77^2}=1[/tex]

Answer:

h = 4, k = 2, a = 5 and b = 8.77.

View image JannetteN575629